"Leader one to base - what's the latest on the opinion polls" [Israeli Prime Minister Mahachem Begin] - Pryor, Geoff, 1944- (1981)
Israel launches an airstrike on the Tanmuz nuclear plant in Iraq destroying almost all of the French Osirak reactors on the site, drawing strong condemnation from around the world including its close US ally. One wonders what the Israelis hope to gain from the exercise.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 10 June 1981.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Begin, Menachem, -- 1913- -- Caricatures and cartoons; Politicians -- Israel -- Caricatures and cartoons; Israel -- Politics and government -- Caricatures and cartoons; Politicians